Simulium (trichodagmia) enderlein, 1934 (diptera: simuliidae): sistemática morfológica e molecular do subgênero e filogeografia de uma espécie - Nascimento, Jeane Marcelle Cavalcante do (Instituto Nacional de Pesquisas da Amazônia - INPA, 2020)
Simuliidae is a family of hematophagous Diptera with worldwide distribution and about 10% of its species are pests or vectors of pathogens to humans and other animals. This family includes the largest complex of structurally uniform species of any group of hematophagous arthropods. Due to their morphological homogeneity, blackflies have proven to be taxonomically difficult thus, considerable effort has been devoted to the resolution of simuliid taxonomy by cytotaxonomic studies of the polytene chromosomes of larval salivary glands and molecular markers. In addition to the large number of cryptic species, another problem related to the morphologic homogeneity in blackfly is related to divergent systematic arrangements in the literature, where systematic decisions were made, in many cases, based on personal opinions, without any clear methodology or hypothesis; only a few broad phylogenetic studies on the family are available. An example of such disagreements is the subgenus analyzed in this thesis, which can be classified as a single subgenus - Simulium (Trichodagmia) - or divided into six subgenera [Simulium (Hearlea), Simulium (Hemicnetha), Simulium (Thyrsopelma), Simulium (Obuchovia), Simulium (Shewellomyia) and S. (Trichodagmia)]. Based on this problem, the objectives of this study were: to investigate the criptic diversity in S. (Trichodagmia) using morphologic, molecular and cytotaxonomic approaches; to describe new taxa in this group; to redescribe poorly described species; to examine the population structure and genetic diversity of one species in S. (Trichodagmia) with broad geographic distribution; to infer a species-level phylogeny of the S. (Trichodagmia) integrating morphological and molecular data. As taxonomic result of the present study two new species were described based on their morphological, molecular and chromosomal features, new taxonomic and biological information were added to two poorly known species, one species was revalidated and redescribed and evidence of cryptic species in some taxa were hypothesized based on molecular and chromosomal data. The phylogenetic analysis did not recover the monophyly of the S. (Trichodagmia) sensu Hernandez (2011) and four subgenera were revalidated.